1981
DOI: 10.1259/0007-1285-54-638-117
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of the growth of the nasopharynx and its contents in normal children

Abstract: The areas of the nasopharynx and its contents have been measured on the lateral cephalometric radiographs of 41 normal children who had been examined at yearly intervals for a minimum of 12 years between the ages of three and 19. The means and standard deviations of the areas of the nasopharynx, the soft tissues and the airway have been calculated for each year from three to 11 and for alternate years to age 19. The size and shape of the soft tissues of individual children are shown to vary from year to year, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
102
2
16

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(137 citation statements)
references
References 11 publications
17
102
2
16
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13] Some studies investigated the effects of growth and development on airway passage dimensions. [32][33][34][35][36] Other studies investigated the pharyngeal size in the subjects having different ANB angles and rotational patterns. 15,37 Taylor et al 34 carried out a longitudinal study on 16 male and 16 female subjects to describe the pattern of bony and soft tissue growth of the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] Some studies investigated the effects of growth and development on airway passage dimensions. [32][33][34][35][36] Other studies investigated the pharyngeal size in the subjects having different ANB angles and rotational patterns. 15,37 Taylor et al 34 carried out a longitudinal study on 16 male and 16 female subjects to describe the pattern of bony and soft tissue growth of the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, tonsils will grow in early childhood. Previous observations suggested that tonsillar and adenoidal tissue enlarge at a faster rate than the bony structures of the nasopharynx during early childhood, and therefore would result in an overall reduction in the upper airway diameter during early childhood (29). However, in healthy non-snoring children, the growth of such tissues is actually proportionate to the somatic growth of the airway, and therefore any deviation from such anticipated growth trajectories would essentially be abnormal (30).…”
Section: Pathophysiology Of Osa In Childhoodmentioning
confidence: 99%
“…Jeans et al (18) reported that the nasopharyngeal dimensions continue to grow rapidly until 13 years of age (18), and then slow until adulthood (19,20).In this study; the age range was 10.50-16.50 years (with an average of 13.26 years) which ensures that the oropharyngeal structures had almost reached adult size.…”
Section: Subjectsmentioning
confidence: 48%
“…Nazofarengeal boyutlar›n 13 yafl›na kadar h›zla geliflti¤i (18), daha sonra eriflkin döne-me kadar yavafllayarak devam etti¤ini belirtilmifltir (19,20). Çal›flmam›za dahil olan bireylerin yafl aral›¤› 10.50-16.50 aras›ndad›r (ortalama 13.26).…”
Section: Discussionunclassified